1975
DOI: 10.1111/j.1744-7348.1975.tb01646.x
|View full text |Cite
|
Sign up to set email alerts
|

Duration of effects of benomyl on growth and wilt (Verticillium dahliae) development in the strawberry, cv. Cambridge Vigour, in relation to time of inoculation

Abstract: Single doses of benomyl, 0.4 g/plant in 1972 or 0.04 g in 1973, were applied in IOO ml water to the surface of the soil in 12.5 cm pots containing Cambridge Vigour strawberry plants, either before inoculation with Verticillium dahliae or at various times up to 56 days afterwards. Pre-inoculation treatments were terminated by washing the potting medium from the roots at the time of inoculation and their effects on pathogenesis and growth were relatively small. Post-inoculation treatments with benomyl prevented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

1976
1976
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…This consisted of equal parts of sieved, partially sterilised (with chloropicrin) field soil and peat-based compost containing V, dahliae. The compost was infested with V, dahliae by thoroughly mixing in a blend of straw cultures of five strawberry isolates (Talboys et al,, 1975), from which coarse material had been removed by sieving (2-mm mesh). The infested soil was stored in a polythene bag in an external store subject to fluctuating temperature conditions.…”
Section: Preliminary Studiesmentioning
confidence: 99%
“…This consisted of equal parts of sieved, partially sterilised (with chloropicrin) field soil and peat-based compost containing V, dahliae. The compost was infested with V, dahliae by thoroughly mixing in a blend of straw cultures of five strawberry isolates (Talboys et al,, 1975), from which coarse material had been removed by sieving (2-mm mesh). The infested soil was stored in a polythene bag in an external store subject to fluctuating temperature conditions.…”
Section: Preliminary Studiesmentioning
confidence: 99%
“…Plant growth. In general the mean volume per plant reached the highest values under treatments which gave the best control of the disease, but there were indications that the larger doses of benomyl caused a slight initial retardation of growth (see also Talboys et al 1975); nevertheless, the final plant size under these treatments was no less than with other effective treatments. The overall effect of the uncontrolled disease was a limitation of plant size, the formation of new leaves being countered by necrosis of the older ones; chemical treatments which controlled the disease led to progressive increases in plant size until September.…”
Section: Comparisons Of Benomyl Thiophanate Methyl and Triarimol Expmentioning
confidence: 96%
“…Talboys & Davies (1976) have shown that mycelium of the pathogen can remain viable after standing for at least 16 wk in a 20 ppm solution of benomyl at either 18 or 23 "C. It is for this reason that pathogenesis is resumed in an infected benomyl-treated plant as soon as the concentration of the chemical falls below the inhibitory level, as was demonstrated by the mid-October bioassays. Talboys et al (1975) emphasized that the concentration of benomyl in the vascular fluids of the host plant cannot exceed that of a saturated solution in soil water, and is unlikely to approach that level. Laboratory studies by Talboys & Davies (1976) have shown that it is possible to select variants of the pathogen which will grow normally in the presence of 12 ppm benomyl, whereas most 'wild type' isolates are inhibited at 0-5 ppm.…”
Section: Crop Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…
Numerous papers describe the high toxicity of benomyl and related fungicides to Verticillium albo-atrum and V. dahliae in vitro and their effectiveness as systemic fungicides in controlling vascular wilts caused by these pathogens (e.g. BoLLEN and FUCHS 1970, ERWIN et al 1968, TALBOYS et al 1975. This effectiveness may be limited in practice by the appearance of insensitive strains whidi will grow in concentrations of the fungicides much higher than those which prevent growth of sensitive strains.
…”
mentioning
confidence: 99%